2017
DOI: 10.3389/fnins.2017.00290
|View full text |Cite
|
Sign up to set email alerts
|

Lights from the Dark: Neural Responses from a Blind Visual Hemifield

Abstract: Here we present evidence that a hemianopic patient with a lesion of the left primary visual cortex (V1) showed an unconscious above-chance orientation discrimination with moving rather than static visual gratings presented to the blind hemifield. The patient did not report any perceptual experience of the stimulus features except for a feeling that something appeared in the blind hemifield. Interestingly, in the lesioned left hemisphere, following stimulus presentation to the blind hemifield, we found an event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…Evidence of residual vision has also been reported with other stimulus features. For example, hemianopic patients, with or without blindsight, have been found to be aware of high contrast, low frequency, high displacement and to a lesser extent colour of stimuli presented in the blind field (Barbur et al, 1999;Bollini et al, 2017;Kentridge et al, 1999Kentridge et al, , 1997Kleiser et al, 2001;Mazzi et al, 2016;Sahraie et al, 2010Sahraie et al, , 1997Weiskrantz et al, 1995). However, as with GY, these seem to reflect blindsight Type 2 rather than phenomenal awareness (Barbur et al, 1999;Sahraie et al, 2010;Sahraie et al, 1997).…”
Section: Riddoch's Syndromementioning
confidence: 99%
“…Evidence of residual vision has also been reported with other stimulus features. For example, hemianopic patients, with or without blindsight, have been found to be aware of high contrast, low frequency, high displacement and to a lesser extent colour of stimuli presented in the blind field (Barbur et al, 1999;Bollini et al, 2017;Kentridge et al, 1999Kentridge et al, , 1997Kleiser et al, 2001;Mazzi et al, 2016;Sahraie et al, 2010Sahraie et al, , 1997Weiskrantz et al, 1995). However, as with GY, these seem to reflect blindsight Type 2 rather than phenomenal awareness (Barbur et al, 1999;Sahraie et al, 2010;Sahraie et al, 1997).…”
Section: Riddoch's Syndromementioning
confidence: 99%
“…Over the last few years, we have extensively tested one hemianopic patient, SL, using several methodologies, ranging from pure behavioral measures (Celeghin et al, 2014, 2015; Mazzi et al, 2016) to EEG/ERPs (Bollini et al, 2017; Sanchez-Lopez et al, 2017; Mazzi et al, 2018b), TMS (Mazzi et al, 2014), TMS-EEG co-registration (Bagattini et al, 2015), and, very recently, fast near-infrared optical signal (Mazzi et al, 2018a).…”
Section: The Case Of Visual Awareness: the Controversial Contributionmentioning
confidence: 99%
“…If V1 and feedback to it are necessary for awareness to emerge, as stated in Lamme's model, a complete lesion to V1 should prevent SL from having perceptual awareness in her blind field. In this respect, SL, tested with a broad variety of stimulus features (Mazzi et al, 2016; Bollini et al, 2017) reported some visual conscious experience of all kind of stimuli presented contralaterally to her lesion in a considerable number of trials (see Mazzi et al, 2017b for a review of older pieces of evidence on conscious experience within the “blind” field of hemianopic patients). Importantly, she could grade conscious visual experience within her “blind” field and the corresponding ERPs revealed differential neural activity with respect to when stimuli remained undetected (Bollini et al, 2017; Sanchez-Lopez et al, 2017; Mazzi et al, 2018b) 1 .…”
Section: The Case Of Visual Awareness: the Controversial Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been termed "blindsight" that is, the ability to detect, localize or discriminate visual stimuli without being aware of them [3]. Over the past 30 years, task-related brain activity [4] and electrophysiological signals [5] have been recorded during visual stimulus presentation to the blind hemifield of these patients with the aim of exploring the neural mechanisms of unconscious vision. In these experiments, patients are asked to give a response even if they cannot consciously perceive anything in the blind visual field.…”
Section: Introductionmentioning
confidence: 99%